Guillan-Barré Syndrome after First Vaccination Dose against COVID-19: Case Report - Čenščák, Daniel; Ungermann, Leoš; Štětkářová, Ivana; Ehler, Edvard (My University, 2021)
A number of neurological complications have been reported after the administration of flu vaccine, including Guillain-Barré syndrome (GBS), especially after vaccination against swine flu. Only facial nerve neuropathy has thus far been reported after vaccination against COVID-19. More recently, there was a case of an elderly woman with GBS. In our report, we describe a case of a 42-year-old, previously almost healthy male who developed sensory symptoms 14 days after the first dose of Pfizer vaccine. One week later, the patient developed right facial nerve palsy and lower limb weakness and was no longer able to walk. Albuminocytological dissociation was detected in the cerebrospinal fluid, and there were inflammatory radicular changes in MRI scans of the lumbosacral spine. EMG indicated significant demyelinating polyradiculoneuritis and no antibodies against gangliosides were demonstrated. A 5-day course of immunoglobulins at a dose of 2 g/kg lead to a significant improvement and the patient was soon able to walk. In conclusion, we report a case of Guillan-Barré syndrome after COVID-19 vaccine in a young patient with a rapid diagnosis and prompt administration of immunoglobulins.
Guillan-Barré Syndrom po první dávce očkování proti COVID-19
Keywords: vaccines; polyradiculoneuritis; ataxia; nerve conduction studies; COVID-19; Guillain-Barré syndrome; immunoglobulins; Guillan-Barré; Syndrom; první; dávce; očkování; proti; COVID-19